Pengembangan Kecerdasan Spiritual Siswa Melalui Pembiasaan Kegiatan Sholat Dhuha Berjamaah Di SMPN 1 Purwosari - Alfiyatul Hasanah; Ali Mohtarom; Askhabul Kirom (EduInovasi: Journal of Basic Educational Studies, 2024)
The purpose of education is to provide moral education with values and norms that will be an example in behaving Education is not only about providing knowledge but also instilling the value of potential intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ), in its condition in the individual. Spiritual intelligence (SQ) has a role in changing spiritual values or religious values such as honesty and trust, This research uses a descriptive qualitative method, the results of the research are in the form of data collection and descriptions or descriptive narratives. Then inter-presenting the data obtained through observation and interviews. The implementation procedure is to carry out arrangements in advance, ask permission with PAI teachers to be able to conduct interviews or collect information so that interview activities can be carried out as expected. The results of the search conducted by the researcher concluded that from all students of SMP Negeri 1 Purwosari as a whole from grade 7 to grade 9 had participated in carrying out the Dhuha prayer activity. Therefore, in this study, from the discussion, there is a positive and significant influence between Dhuha prayer on the Spiritual Intelligence (Spiritual Quotient) of students of SMP Negeri 1 Purwosari. With this, it can be concluded that the abilities carried out by students greatly affect the students' Spiritual Quotient. From the observations made and some findings obtained by the researchers, it shows that the results of the measure of discipline, behavior in learning at school and all habituation activities can also be applied at home with good results.